(untitled) (Research, Society and Development, 2025)
This essay investigates the relationships between body, space, and power in the school environment, taking as its starting point the memory of the punishment of “smelling the wall.” The objective is to critically analyze the disciplinary mechanisms that immobilize and silence bodies, while proposing, in turn, a pedagogy sensitive to movement and expressiveness. Methodologically, the text articulates theoretical reflections, based on authors such as Foucault, Butler, Hooks, and Massumi, and engages with works by performance artists, such as Santiago Sierra and Marina Abramović, who re-signify the wall as a political and poetic medium. The results highlight the potential of dance and performance as practices capable of decolonizing the body and subverting institutional control logics. It is concluded that the reinvention of the school space involves the adoption of a performative, relational, and affective education, in which bodies can critically occupy the environment, transforming it into a territory of invention and freedom.